Virgil’s Hero, Turnus: Maffeo Vegio’s and Pier Candido Decembrio’s Supplements to the Aeneid (with a New Edition and Translation of Decembrio) - Gervais, Kyle (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2022)
I examine a dialogue between the Renaissance Supplements to Virgil’s Aeneid by Pier Candido Decembrio and Maffeo Vegio. I argue that Decembrio’s short poem is not unfinished but instead provides the Iliadic ending to the Aeneid that Virgil withholds, namely a lament over Turnus’s body to match the lament over Hector at the end of Iliad 24. I then argue that Decembrio’s poem presents us with a dangerously unstable situation in Italy, dominated by commemorations of Turnus in such heroic terms that they threaten to displace Virgil’s hero Aeneas from primacy in his own story. Vegio’s response “corrects” this portrayal of Turnus in favour of a more orthodox Virgilian narrative in which Turnus is a tragically misguided enemy of Aeneas’s divine mission to Italy. I conclude with a new edition and translation of Decembrio’s Supplement, drawing on both of the extant manuscripts and addressing several textual difficulties.